Ibibio Libation Performances and Worldview (2013)
Libation among the Ibibio involves invocations, incantations and supplications to the gods and ancestors through which their world view is expressed. While aspects of libation such as sacrifices, chants, rites and rituals, which emphasis on contents, have been adequately researched, performance of libation has not been elaborately studied, relevant as it is in revealing the cultural values of the Ibibio people. This study, therefore, examines the performance properties and world view of Ibibio people in their libation performances. The study applies Charles Peirce‟s semiotic and Richard Schechner‟s performance theories. Purposive and snowball techniques were used in selecting fifteen libation performances covering sacrifice (3), coronation (2), purification (1), planting (1), harvest (1), appeasement (2), dispute (1), welcome (2), puberty (1) and naming rite (1), collected From Uyo (5), Itu (1), Nsit (1), Eket (2), Ibesikpo (1) Ini (3) and Ikono (2). These performances were transcribed and translated into English. Four Focus Group Discussions (FGDs) involving Chiefs (8), academics (3) and a combination of artisans, traders and youths, aged 25-35 (6) were held. In-depth interviews were conducted with libation performers (4), academics (3) and elderly members (3) of Ibibio society. Data were subjected to semiotic and critical analyses. Ibibio libation performances reveal indexical, iconic, and symbolic signs. Schnapps, ufọfọb (native gin), other hard drinks, nnʌk enañ (cow horn), ukpok/iko (gourd) or glass indexicates sacrifices. Pointing up and down to denote heaven and earth combines with verbal deixis in personal pronouns such as ami (I), nnyin (we) and mbufo (you), to indexicate the Ibibio source of strength. While nnʌk eniin (elephant tusk) and ekere (gong) are iconic of coronation performances, palm-wine and palm-oil are iconic of appeasement; animals are iconic of sacrifices. Ukpok/iko (gourd) symbolises oneness, palm-oil and eggs symbolise peace and nnʌk eniin (elephant tusk) symbolises royal authority. Ibibio libation performances are ritualistic, but some are more intense in contents and props. Performances from Ini and Ikono are more esoteric than those from the urban settings. Spatial and temporal settings of the performances vary according to context: while appeasement performances to Amasa, the water goddess, are set by the sea-side at midnight, with fowls, eggs, white basins, schnapps and priests dressed in white, appeasement performances for the earth deities are performed at shrines or spots of desecration, in the evenings with items like ufọfọb (native gin), other hard drinks and palm-wine. The insistence on schnapps for the water goddess underscores Ibibio understanding of schnapps as a foreign drink. Similarly, coronation performances are performed at designated spiritual arenas, while routine worship, welcome, naming or puberty rites are performed at homes with performers dressed in traditional attire. The select texts exhibit repetition and metaphor as devices used in exploring narrative properties such as plea, confidence and affirmation. Libation performances in Ibibio society which utilise symbolic drinks, objects and props reflect the mores of the people. Thus, they reveal a communion with the gods and ancestors manifested in theatrical aesthetic that portrays the cultural values and world view of the Ibibio.